Factors impeding the industrialized building system (IBS) implementation of building construction in Malaysia - Md. Ali, Massofia; Abas, Nor Haslinda; Mohd Affandi, Haryanti; Abas, Nor Ain (Science Publishing Corporation, 2018)
In Malaysian construction industry, Industrialised Building System (IBS) has been introduced to replace the traditional construction method. While the government has been making significant efforts to encourage the IBS adoption, the uptake of IBS in Malaysia construction projects remains low. This study seeks to identify the barriers to the uptake of IBS and to propose the strategies to enhance the implementation IBS in Malaysian housing construction process from the perspectives of consultants. Interviews were conducted with five selected experienced individuals who were working with consultants (civil and structure engineer and quantity surveyor). The results revealed that, lack of knowledge and insufficient skilled workers are the main factors that impede the IBS uptake in Malaysia. Meanwhile, the most strategy proposed by the interviewees is to increase the facilities and incentives in order to expand research and development in IBS